IMPLIKASI PASAL 114 UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA DAN PERATURAN PEMERINTAH NOMOR 10 TAHUN 2021 TENTANG PAJAK DAERAH DAN RETRIBUSI DAERAH DALAM RANGKA MENDUKUNG KEMUDAHAN BERUSAHA DAN LAYANAN DAERAH TERHADAP KEUANGAN NEGARA DAN KEUA - Robby Alexander Sirait (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2021)
Article 114 of the law of 2020 on job creation has amended several articles in law number 28 of 2009 on local taxes and retribution. These changes will have an impact to change of authority regarding local taxes and retribution, and also to state and local finances. This paper aims to know the changes of authority regarding local taxes and retribution and the implications of these changes to state and local finances. This paper is prepared with a normative juridical approach. The results of the study conclude that the changes of authority have significantly eliminate the authority of district/city government regarding local taxes and retribution which will have implications for decreasing local revenue and spending, worsening degree of fiscal decentralization, and increasing local financial dependence.